PROFITABILITAS, LIKUIDITAS, DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Tresna Nour Fauziah; Dini Arifian; D. Muhamad Yamin (The Asia Pacific Journal Of Management Studies, 2026)
This study aims to examine the influence of profitability (measured by Return on Equity/ROE), liquidity (measured by Current Ratio/CR), and debt policy (measured by Debt to Equity Ratio/DER) on firm value (measured by Price-Earnings Ratio/PER). This is a quantitative study. A saturated sampling method was employed, utilizing a dataset of 32 observations from four state-owned (BUMN) banks listed on the Indonesia Stock Exchange during the 2017–2024 period. Multiple linear regression analysis was conducted using SPSS version 27. The results indicate that, individually, debt policy has a significant effect on firm value, whereas profitability and liquidity do not. However, when considered simultaneously, profitability, liquidity, and debt policy collectively influence firm value